Peran Guru PAI dalam Pengembangan Moderasi Beragama dan Toleransi - Yusuf, Yusuf Qardhawi Ridho Sarky; Supratama, Riky (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the role of Islamic Education (PAI) teachers in fostering religious moderation and tolerance among students in response to growing challenges related to diversity in educational settings. The objective of this research is to describe the pedagogical strategies and instructional methods employed by PAI teachers, as well as to identify the supporting and inhibiting factors that shape the effectiveness of promoting moderate and tolerant attitudes. Utilizing a qualitative literature review approach, this study conducts a critical analysis of relevant academic sources. The findings indicate that PAI teachers play a pivotal role in cultivating moderate and tolerant behavior through learning approaches that emphasize dialogical engagement, value internalization, and strengthened understanding of diversity. Supporting factors include an inclusive school culture and teachers’ professional awareness of the importance of religious moderation. Conversely, inhibiting factors encompass limited pedagogical resources and the influence of external extremist ideologies. Overall, the study underscores the strategic position of PAI teachers in developing a harmonious and diversity-oriented educational environment.